2021
DOI: 10.3390/ijerph18084148
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Playing Formation on Physical Demands and Technical-Tactical Actions According to Playing Positions in an Elite Soccer Team

Abstract: The aim of this study was to examine the differences in the physical demands and technical-tactical actions encountered by soccer players between two playing formations (1-4-2-3-1 and 1-4-4-2) for each playing position. Twenty-three professional male soccer players who played 31 official matches participated in this study. Players were classified according to their playing position: central defenders (CD), wide defenders (WD), central midfielders (CM), wide midfielders (WM), offensive midfielders (OM) and forw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
62
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(66 citation statements)
references
References 47 publications
4
62
0
Order By: Relevance
“…Other studies by Dellal et al (2010 , 2011) reported that forwards sprinted the greatest distance than other playing positions during the French First League, the Spanish LaLiga, and the English FA Premier League soccer matches. These contradictions may be explained by the fact that each team has a specific playing formation, opposition level, tactics, and physical fitness of players ( Al’Hazzaa et al, 2001 ; Aquino et al, 2017 ; Sarmento et al, 2018 ; Slimani et al, 2019 ; Arjol-Serrano et al, 2021 ). Therefore, it seems that practitioners would adopt position-specific training programs for their players.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies by Dellal et al (2010 , 2011) reported that forwards sprinted the greatest distance than other playing positions during the French First League, the Spanish LaLiga, and the English FA Premier League soccer matches. These contradictions may be explained by the fact that each team has a specific playing formation, opposition level, tactics, and physical fitness of players ( Al’Hazzaa et al, 2001 ; Aquino et al, 2017 ; Sarmento et al, 2018 ; Slimani et al, 2019 ; Arjol-Serrano et al, 2021 ). Therefore, it seems that practitioners would adopt position-specific training programs for their players.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, if a player played on two positional roles (e.g., ‘center back in 4-4-2’ and ‘full back in 4-4-2’ ) while the formation (e.g., 4-4-2) did not change, he was included in the sample. A minimum of four games per positional role was used to account for the variability of technical performance between matches and to minimize the influence of contextual factors ( Bradley et al, 2011 ; Aquino et al, 2019 ; Arjol-Serrano et al, 2021 ). As a result, 13 players were included in the study sample.…”
Section: Methodsmentioning
confidence: 99%
“…The technical performance was analyzed using the number of dribblings, passes, and ball possessions. Throughout previous studies that investigated technical match performance, ball possessions, passes and dribblings were the most frequently analyzed parameters ( Bradley et al, 2011 ; Aquino et al, 2019 ; Arjol-Serrano et al, 2021 ). Based on the covered distance of the ball, passes were divided into three categories [short (<10 m), medium (10 ≥ 30 m), long (>30 m)].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations